2020
DOI: 10.1101/2020.08.05.237610
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CRISPR/Cas9 technology abolishes theBCR/ABL1oncogene in chronic myeloid leukemia and restores normal hematopoiesis

Abstract: Chronic myeloid leukemia (CML) is a hematopoietic stem cell disease produced by a unique oncogenic event involving the constitutively active tyrosine kinase (TK) BCR-ABL1. TK activity explains most features of CML, such as tumor development and maintenance. TK-inhibitory (TKI) drugs have changed its prognosis and natural history. Unfortunately, since ABL1 gene remains unaffected by TKIs, most patients should be treated with lifelong oral medication, resistant mutations arise and adverse effects occur during tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 61 publications
0
5
0
1
Order By: Relevance
“…In this strategy, after electroporation of the CRISPR components, ex vivo edited hematopoietic stem/progenitor cells of the patients are transplanted back. Vuelta et al (2020) used electroporation for the delivery of the Cas9 RNP complex for disrupting BCR/ABL1 oncogene in leukemic stem cells. Transplantation of ex vivo edited cells restored normal hematopoiesis in NSG mice.…”
Section: Physical Deliverymentioning
confidence: 99%
“…In this strategy, after electroporation of the CRISPR components, ex vivo edited hematopoietic stem/progenitor cells of the patients are transplanted back. Vuelta et al (2020) used electroporation for the delivery of the Cas9 RNP complex for disrupting BCR/ABL1 oncogene in leukemic stem cells. Transplantation of ex vivo edited cells restored normal hematopoiesis in NSG mice.…”
Section: Physical Deliverymentioning
confidence: 99%
“…Edited patient-derived CD34+ are capable of regenerating normal hematopoiesis in the bone marrow niche of NOD/SCID mice. [104] In 2018, Wenli Feng's group demonstrated that other genome-editing nucleases, like ZFN nucleases, achieved the abrogation of the BCR/ABL1 oncogene [95]. Using a pair of ZFNs targeting the exon 1 of BCR, a premature stop codon was created triggering a truncated oncoprotein.…”
Section: Crispr/cas9mentioning
confidence: 99%
“…Finally, Vuelta et al recently reported their design of a new CRISPR/Cas9 short-deletion system that efficiently interrupts the BCR/ABL1 oncogene in murine and human cell lines and, for the first time, in primary leukemic stem cells Sca1+ from a CML mouse model and CD34+ from human CML patients [ 104 ]. They demonstrated that CRISPR/Cas9-edited LSCs had impaired tumorigenic activity and fully restored capacity for multipotency.…”
Section: Crispr Gene Therapy In CMLmentioning
confidence: 99%
“…This new strategy induces a large genomic deletion in the tumor cells and shows great inhibition-specific tumor growth in a K562 xenograft model. Finally, Vuelta et al recently reported their design of a new CRISPR/Cas9 short-deletion system that efficiently interrupts the BCR/ABL1 oncogene in murine/human cell lines and, for the first time, in primary leukemic stem cells (CD34+) from a CML mouse model and from human CML patients [80]. They demonstrated that CRISPR/Cas9-edited LSCs had impaired tumorigenic activity and fully restored capacity for multipotency.…”
Section: Crispr Gene Therapy In CMLmentioning
confidence: 99%